An Introduction to Food Grade Nanoemulsions - Dasgupta, Nandita (Environmental Chemistry for a Sustainable World,, 2018)
This book provides authentic and comprehensive information on the concepts, methods, functional details and applications of nano-emulsions. Following an introduction to the applications of nanotechnology in the development of foods, it elaborates on food-grade nano-emulsion and their significance, discusses various techniques and methods for producing food-grade nano-emulsion, and reviews the main ingredient and component of food-grade nano-emulsions. Further, the book includes a critical review of the engineering aspect of fabricating food-grade nano-emulsions and describe recently developed vitamin encapsulated nano-systems. In closing, it discuss the challenges and opportunities of characterizing nano-emulsified systems, the market risks and opportunities of nano-emulsified foods, and packaging techniques and safety issues - including risk identification and risk management - for nano-foods. The book offers a unique guide for scientists and researchers working in this field. It will also help researchers, policymakers, industry personnel, journalists and the general public to understand food nanotechnology in great detail.